Application of Lasers in Vascular Anomalies - Patil, Uddhav Anandrao (Indian Journal of Plastic Surgery, 2023)
Laser technology has significantly improved giving better results, which in turn has led to an increase in the indications for laser therapy. Vascular anomalies comprise vascular tumors and malformations. They are classified according to the type of vessels involved including arteries, capillaries, postcapillary venules, veins, lymphatic vessels, and a combination of two or more of these. Laser needs a chromophore to get absorbed and act. Hemoglobin, both oxy and deoxy, is one of the naturally occurring chromophore that is abundant in vascular lesions. Therefore, in most of the vascular lesions, lasers can bring improvement of a varying degree, while for superficial hemangiomas and port wine stain (PWS) laser treatment is now the standard of care. However, even though there is increase in the use of lasers in clinical practice, many surgeons are still unaware of its versatility and they are unsure about its safety. This article provides a brief overview of laser and intense pulsed light (IPL) technology, and describes the key principles in using these energy sources in vascular malformations. Readers are also familiarized with possible adverse effects and measures to prevent and treat them.
Keywords: laser treatment; vascular malformations; vascular anomalies; vascular lasers; hemangioma